Jakob Linzbach on his life and work - Moret, Sébastien (Sign Systems Studies, 2019)
The Estonian scholar Jakob Linzbach is primarily known for having published, in 1916, a Russian-language book with the title The Principles of Philosophical Language: An Attempt at Exact Linguistics. In this book, and in his other published and unpublished works, he aimed at creating a universal written language in which mathematics and images would mix. Linzbach’s ideas have raised awareness among people from different (scholarly) fields – semiotics, interlinguistics, philosophy, cinema theory, informatics, etc. However, not much has been published about Linzbach’s life. In one of his manuscripts kept in Tartu, there is a chapter that can be considered an autobiography and that provided, in the pencil of Linzbach himself, information about his life and work. This text is edited, translated into English and commented here for the first time.